Instrumen-Instrumen Investasi Syariah Sebagai Alternatif Investasi Bodong - Kulsum, Ummi; Tamimah, Tamimah (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
This study illustrates the number of cases of investment that duplicates the websites of entities that have permission so that it is as if the website officially belongs to the entity that has permission. Therefore, one way that prospective investors avoid the existence of investment bodong is that prospective investors must know whether the company has been registered with the Financial Services Authority (OJK) or not? Therefore, this study aims to look at sharia investment options in an effort to avoid investment bodong. This research is a literature study and a type of qualitative descriptive research. Qualitative descriptive is a data in the form of words, images and not numbers. This is due to the application of qualitative methods. In addition, all the data collected is likely to be the key to what has been researched. Thus, the research report will contain citations and data collection to give an idea of the presentation of the report. The result of this research is that there are five sharia investment options that have been registered with OJK, so that we avoid investments, including: Sharia Stock Investment, Sharia Mutual Fund Investment, Sharia Deposit, Retail Sukuk and Gold. This research uses qualitative descriptive methods. Keywords: Sharia Investment, Alternative, Bodong Investment